2020
DOI: 10.1186/s12992-020-00621-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental health impacts among health workers during COVID-19 in a low resource setting: a cross-sectional survey from Nepal

Abstract: Background Health care workers exposed to COVID-19 might be at increased risk of developing mental health problems. The study aimed to identify factors associated with anxiety, depression and insomnia among health workers involved in COVID-19 response in Nepal. Methods This was a cross-sectional web-based survey conducted between April 26 and May 12, 2020. A total of 475 health workers participated in the study. Anxiety and depression were measured using a 14-item Hospital Anxiety and Depression Scale (HADS:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
260
7
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(302 citation statements)
references
References 44 publications
27
260
7
8
Order By: Relevance
“…The shortage of PPE wasn't statistically significant in our study, which might be due to adopting the participants with the current situation. However, several studies have reported this as a considerable source of distress among healthcare workers [25,29,30] and have specified the need to equip these frontline workers with adequate resources which can strengthen their overall work performance with better psychological outcomes [25,31]. Lack of protective measures can create a sense of insecurity and thus imposes the healthcare workers to higher exposure to infections.…”
Section: Plos Onementioning
confidence: 99%
“…The shortage of PPE wasn't statistically significant in our study, which might be due to adopting the participants with the current situation. However, several studies have reported this as a considerable source of distress among healthcare workers [25,29,30] and have specified the need to equip these frontline workers with adequate resources which can strengthen their overall work performance with better psychological outcomes [25,31]. Lack of protective measures can create a sense of insecurity and thus imposes the healthcare workers to higher exposure to infections.…”
Section: Plos Onementioning
confidence: 99%
“…12 A study conducted in Nepal showed that 41.9% of health workers had symptoms of anxiety, 37.5% had depressive symptoms, 33.9% had symptoms of insomnia and more than half of the health workers faced stigma. 13 A study in India reported that the knowledge and practice towards COVID-19 pandemic among people is good but still there was a gap in right perception. 14 Similarly, in the USA and the UK, people had important misconceptions about COVID-19 whereas, in Nepal, a study reported that the overall knowledge of COVID-19 was high and the majority of people had a positive perception towards universal safety measures.…”
Section: Introductionmentioning
confidence: 99%
“… 12 A study conducted in Nepal showed that 41.9% of health workers had symptoms of anxiety, 37.5% had depressive symptoms, 33.9% had symptoms of insomnia and more than half of the health workers faced stigma. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Pooled prevalence of anxietyA total of 31 studies reported the prevalence of anxiety during COVID-19 in different samples from South Asian countries[46][47][48][49][50][51][52][53][54][55][56]58,59,[61][62][63][64][65][66]68,69,[71][72][73][74][75][76][77][78][79][80] . These studies used different scales to measureanxiety in respective samples, including the Generalized Anxiety Disorder 7-item (GAD-7) scale (n = 16), Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%